2023
DOI: 10.3390/cancers15164173
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecules against Metastatic Tumors: Concrete Perspectives and Shattered Dreams

Massimo Serra,
Davide Rubes,
Sergio Schinelli
et al.

Abstract: Metastasis is the main cause of anti-cancer therapy failure, leading to unfavorable prognosis for patients. The true challenge to increase cancer patient life expectancy by making cancer a chronic disease with periodic but manageable relapses relies on the development of efficient therapeutic strategies specifically directed against key targets in the metastatic process. Traditional chemotherapy with classical alkylating agents, microtubule inhibitors, and antimetabolites has demonstrated its limited efficacy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…Lapatinib also crosses the blood brain barrier, because it has been shown that brain metastases were decreased to 50%-53% of control in xenografted mice with metastatic breast cancer (98). Noteworthy, lapatinib is also under clinical investigations for several other solid tumours with high EGFR and/or HER2 expression (103). The present study found that lapatinib decreased tumour cell migration, invasion and reproductive growth, which suggests that the drug may be developed as an adjuvant therapy in the prevention of UM metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Lapatinib also crosses the blood brain barrier, because it has been shown that brain metastases were decreased to 50%-53% of control in xenografted mice with metastatic breast cancer (98). Noteworthy, lapatinib is also under clinical investigations for several other solid tumours with high EGFR and/or HER2 expression (103). The present study found that lapatinib decreased tumour cell migration, invasion and reproductive growth, which suggests that the drug may be developed as an adjuvant therapy in the prevention of UM metastases.…”
Section: Discussionmentioning
confidence: 99%